Measuring the Concentration of Serum Syndecan-1 to Assess Vascular Endothelial Glycocalyx Injury During Hemodialysis - Kusuzawa, Keigo; Suzuki, Keiko; Okada, Hideshi; Suzuki, Kodai; Takada, Chihiro; Nagaya, Soichiro; Yasuda, Ryu; Okamoto, Haruka; Ishihara, Takuma; Tomita, Hiroyuki; Kawasaki, Yuki; Minamiyama, Toru; et al. (Frontiers in Medicine, 2021)
Glycocalyx is present on the surface of healthy endothelium, and the concentration of serum syndecan-1 can serve as an injury marker. This study aimed to assess endothelial injury using serum syndecan-1 as a marker of endothelial glycocalyx injury in patients who underwent hemodialysis. In this single-center, retrospective, observational study, 145 patients who underwent hemodialysis at the Gifu University Hospital between March 2017 and December 2019 were enrolled. The median dialysis period and time were 63 months and 3.7 h, respectively. The serum syndecan-1 concentration significantly increased from 124.6±107.8 ng/mL before hemodialysis to 229.0±138.1 ng/mL after hemodialysis (P<0.001). Treatment with anticoagulant nafamostat mesylate inhibited hemodialysis-induced increase in the levels of serum syndecan-1 in comparison to unfractionated heparin. Dialysis time and the change in the syndecan-1 concentration were positively correlated. Conversely, the amount of body fluid removed and the changes in the syndecan-1 concentration were not significantly correlated. The reduction in the amount of body fluid removed and dialysis time inhibited the change in the syndecan-1 levels before and after hemodialysis. In conclusion, quantitative assessment of the endothelial glycocalyx injury during hemodialysis can be performed by measuring the serum syndecan-1 concentration, which may aid in the selection of appropriate anticoagulants, reduction of hemodialysis time, and the amount of body fluid removed.